Outcomes of coronary rotational atherectomy in patients with reduced left ventricular ejection fraction. Issue 4 (October 2020) - Zhang, Hui-Ping; Zhao, Ying; Ai, Hu; Li, Hui; Tang, Guo-Dong; Zheng, Nai-Xin; Sun, Fu-Cheng
Objective: We evaluated the safety and efficacy of rotational atherectomy (RA) in patients with a reduced left ventricular ejection fraction (LVEF). Methods: In total, 140 consecutive patients with severe coronary artery calcification (CAC) who underwent RA were retrospectively enrolled. Patients were grouped based on LVEF: ≤35% (n = 10), 36% to 50% (n = 11), and >50% (n = 119). We assessed procedural success and periprocedural complication rates as well as the incidences of in-hospital and 2-year major adverse cardiac events (MACEs), defined as hospitalization for myocardial infarction and worsening heart failure, target vessel revascularization, and cardiac death. Results: Procedural success was achieved in nearly all patients in each group. Most periprocedural complications were minor, and major complications were uncommon. The 2-year MACE rate was significantly higher in the LVEF ≤35% than LVEF >50% group (40.0% vs. 6.7%, respectively). Multivariable regression analysis revealed that the LVEF was the only independent predictor of 2-year MACEs in patients who underwent RA. Conclusions: Patients with a reduced LVEF who underwent RA had procedural success rates similar to those of patients with preserved left ventricular systolic function. The LVEF might be an independent predictor of 2-year MACEs in patients with severe CAC after percutaneous coronary intervention following RA.